IRAN: ARMED FORCES AND SECURITY POLICY - MINASIAN, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2004)
The armed forces occupy a prominent place in the state structure, playing an active role in the country’s socio-political life. Their main distinguishing feature is that for more than 20 years that have passed since the Islamic Revolution began in Iran, they have been comprised of two parallel and independent structures—the Army (Artesh) and the Iranian Islamic Revolutionary Guards Corps (IRGC)—Pasdaran Inqilab. On the political level, it should be noted that the armed forces’ loyalties lie with the regime more than with the general population, a democratic system, or the nation as an abstraction. The main exceptions here are Turkey, where the military sees itself as the guardian of the republic, and Israel.Formed by the ruling regime, they are nonetheless strongly influenced by the ideas of the Islamic Revolution and are more wedded to ideology than to the regime or even the state. This is especially pronounced in the IRGC, where Islamic ideology has a greater impact, than in Artesh.1 The preamble to the republic’s Constitution says: “In the formation and equipping of the country’s defense forces, due attention must be paid to faith and ideology as the basic criteria. Accordingly, the Army of the Islamic Republic of Iran and the Islamic Revolutionary Guards Corps are to be organized in conformity with this goal, and they will be responsible not only for guarding and preserving the frontiers of the country, but also for fulfilling the ideological mission of jihad in God’s way; that is, extending the sovereignty of God’s law throughout the world.” The fundamental concepts underlying the organization of the armed forces are formulated in Chapter IX, Part II of the Constitution, The Army and the Iranian Islamic Revolutionary Guards Corps (Arts 143-151). Furthermore, military organization is regulated by a code of laws and legislative acts. Khomeini’s commandments and the principles enshrined in the Constitution as well as in other documents concerning the armed forces require an all-out political-ideological effort in the military sphere where a distinctive religious and political-ideological indoctrination system was put in place.importantly, its operation is closely coordinated with counterpart civilian structures.2 Amid the on-going problems with the acquisition of modern weapons, the ideological and religious indoctrination system has in fact become a major factor in the organization of operationally effective armed forces in the post-revolutionary period.